Redefining Musical Creativity: The Pipa Solo Tradition in Republican China and During the Mao Era - Ho Chak Law (Analytical Approaches to World Music, 2022)
As a plucked lute that has one of the most longstanding solo traditions in China, the pipa has been treated as a symbol of authentic Chineseness in modern times by Chinese and non-Chinese people alike. That said, by reviewing how the pipa solo tradition evolved during the twentieth century through an analysis of three representative musical examples, this article argues that the pipa was subject to the torrent of modernization and nationalism, as exemplified in a number of redefined means to express musical creativity.